Efek integrated nutrition programme terhadap profil lipid dan komposisi tubuh pada remaja obes - Martha Ardiaria; Erin Ratna Kustanti; Ria Purnawian Sulistiani; Etika Ratna Noer (Jurnal Gizi Klinik Indonesia, 2019)
The effect of integrated nutrition programme on lipid profile and body composition among adolescent obesityBackground: Obesity is a serious public health issue increasingly in the adolescent. Obesity in adolescence will continue into adulthood and lead to later health problems. The adolescent has high food dense calories which high fat and low in fiber that can trigger obesity. Integrated Nutrition Programme (INP) is an intervention model for obesity with an emphasis on a low-calorie diet, low fat, high fiber, moderate physical activity, and nutrition counseling.Objective: This study aimed to evaluate the effect of INP on lipid profile and body composition in obese adolescents.Methods: Quasi-experimental study pre-post trial design with a total of subjects 18 obese adolescents. Duration of intervention in subjects for four weeks with a hypocaloric diet, low fat, high fiber, and prepared by a dietician. Moderate exercise and dietary counseling were conducted on the subject regularly. Bodyweight (BW) and waist circumference (WC) were monitored once a week. Food record intake is done before and during the intervention.Results: The mean weight loss of 1.55 kg. There is a difference in mean BW, WC, and BMI (p<0.01), whereas there were no significant differences in lipid profiles and body composition between before and after the intervention.Conclusions: INP can significantly affect weight loss, BMI, and WC as well as a significant increase in physical activity.